Alexander, Agathoi Daimones, Argives and Armenians - Christian Djurslev (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2018)
Intriguing and complex traditions are preserved about Alexander and the agathos daimon house-snakes of Alexandria by Phylarchus, the Alexander Romance, ps.-Epiphanius and the Chronicon Paschale. These bear upon both a foundational myth and upon a related cultural practice. New light is shed on these traditions by some striking comparative folkloric evidence gathered in Armenia at the end of the nineteenth century. In primis, the Armenians’ practice of addressing their friendly house snakes as ‘Armenians’ suggests that the Alexandrians’ practice of addressing their own friendly house snakes as ‘Argives’ entailed a notion that they were themselves, somehow, ‘Argive’ in origin, a notion that can be evidenced in several further ways.